PAYMENT FOR ECOSYSTEM SERVICES AS A LOCAL POLICY FOR STRENGTHENING FAMILY FARMING (SÃO PAULO, BRAZIL) - Fernandes, Jamily da Silva [UNESP]; Oliveira, Renata Evangelista de [UNESP]; Sais, Adriana Cavalieri; Borsatto, Ricardo Serra (My University, 2022)
This study evaluates two interrelated and complementary municipal programs, one aimed at strengthening family farming and good land-use practices, and the other at paying for environmental services, aiming at forest restoration linked to the provision of water for public supply in Louveira (SP-BRAZIL). The aim was to identify through local stakeholders the factors that influence the operational environment of these programs, limiting or promoting their effectiveness, categorizing them as strengths, weaknesses, potentialities, or threats. Semi-structured interviews were conducted with representatives of strategic organizations, and the factors analyzed were presented using a SWOT matrix. The results indicated two factors as threats to the continuity of programs: dependence on political decisions and their funding source. Practicing sustainability through good practices, environmental concerns, and the payment of subsidies to farmers were the main strengths identified. All the weaknesses and some of the threats refer to the low participation and understanding of farmers regarding the programs, which indicates that strategies are needed to foster farmers’ engagement, making them more than just “recipients” of the programs.
PAGAMENTO POR SERVIÇOS AMBIENTAIS COMO ESTRATÉGIA PARA FORTALECIMENTO DA AGRICULTURA FAMILIAR EM UM MUNICÍPIO PAULISTA
Keywords: ESP; Local development policies; SDGs; SWOT matrix